Extent and nature of poverty and correlates of development - a spatial analysis with reference to northern states of Malaysia - Vyas, Ravindra Nath; Yusof, Rohana; Abdullah, Norehan (2018)
Poverty invariably addressed at the very beginning and evaluated at the end of development planning to set and assess the goals achieved across the targeted strata of people and geographic space. The development strategy, executed for Malaysia or for northern part of peninsular Malaysia, though aimed to integrate forces and sectors to accelerate development, but not keeping the issue of poverty out of focus.Malaysian experience of eliminating poverty in the country is highly acclaimed achievement but it is not completely vanished from the landscape. It continues to prevail in certain areas and among groups characterised by constraining conditions within the imposing designs of gained and perfecting the development processes.The remnants of poverty, its forms and determinants are being studied ceaselessly almost in all sub-fields of social sciences in the country as well as in other parts of the world for pragmatic solutions or for academic deliberations but the incidence of poverty related to individuals is not fully interpreted by associating it to space characteristics and to components of grand design of development strategies.The present paper is an exercise to depict geographic extent of poverty along with the characteristics of inflicted people and to examine how poverty continues to indignant people in States of Perlis, Kedah, Penang and Perak.The study is based on EKasih data related to classified poor households for the year 2015.For spatial depiction and analysis the data are aggregated at Mukim level to relate poverty scenario with other developmental characteristics of the region.Thus, the poverty and it’s correlates are discussed as phenomenon exist across the region with its hard to break relations of geographic, social, economic, and political nature.Findings of the study are important as the issue of poverty is discussed to bring the actual distribution overs apace and answer to eradicate it to achieve the national goal of development.